A Novel PET Imaging Using 64Cu-Labeled Monoclonal Antibody against Mesothelin Commonly Expressed on Cancer Cells. (25th March 2015) - Kobayashi, Kazuko; Sasaki, Takanori; Takenaka, Fumiaki; Yakushiji, Hiromasa; Fujii, Yoshihiro; Kishi, Yoshiro; Kita, Shoichi; Shen, Lianhua; Kumon, Hiromi; Matsuura, Eiji
Abstract : Mesothelin (MSLN) is a 40-kDa cell differentiation-associated glycoprotein appearing with carcinogenesis and is highly expressed in many human cancers, including the majority of pancreatic adenocarcinomas, ovarian cancers, and mesotheliomas, while its expression in normal tissue is limited to mesothelial cells lining the pleura, pericardium, and peritoneum. Clone 11-25 is a murine hybridoma secreting monoclonal antibody (mAb) against human MSLN. In this study, we applied the 11-25 mAb to in vivo imaging to detect MSLN-expressing tumors. In in vitro and ex vivo immunochemical studies, we demonstrated specificity of 11-25 mAb to membranous MSLN expressed on several pancreatic cancer cells. We showed the accumulation of Alexa Fluor 750-labeled 11-25 mAb in MSLN-expressing tumor xenografts in athymic nude mice. Then, 11-25 mAb was labeled with 64 Cu via a chelating agent DOTA and was used in both in vitro cell binding assay and in vivo positron emission tomography (PET) imaging in the tumor-bearing mice. We confirmed that 64 Cu-labeled 11-25 mAb highly accumulated in MSLN-expressing tumors as compared to MSLN-negative ones. The 64 Cu-labeled 11-25 mAb is potentially useful as a PET probe capable of being used for wide range of tumors, rather than 18 F-FDG that occasionally provides nonspecific accumulation into the inflammatory lesions.